2017
DOI: 10.1039/c7ra10778a
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-induced photocatalytic degradation of gas-phase acetaldehyde with platinum/reduced titanium oxide-loaded carbon paper

Abstract: Visible light-induced degradation of gas-phase acetaldehyde (CH 3 CHO) is investigated using O-deficient reduced TiO 2Àx -loaded carbon paper. The carbon paper is synthesized by the pyrolysis of a filter paper, and the reduced TiO 2Àx is prepared by the magnesiothermic reduction of commercial anatase TiO 2 . The surface areas of the non-carbonized filter paper and carbon papers obtained by carbonization at 400, 600, 800, and 1000 C are 4. (l > 420 nm), attributed to the efficient adsorption of gas-phase CH 3 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A uniform mixture of a-TiO 2 powder (Sigma-Aldrich, d < 25 nm, 4 g) and Mg powder (Samchun, 1.21 g) (molar ratio of 1:1) was placed in a quartz tube furnace and then heated at 650 °C for 8 h under the flow of H 2 /Ar (5 vol % H 2 ). After the reductive heating with Mg metal, the heated sample was stirred with 2.0 M HCl solution for 4 h to selectively etch out the MgO phase in order to obtain MgO-free reduced TiO (named T1) with high porosity. …”
Section: Experimental Methodsmentioning
confidence: 99%
“…A uniform mixture of a-TiO 2 powder (Sigma-Aldrich, d < 25 nm, 4 g) and Mg powder (Samchun, 1.21 g) (molar ratio of 1:1) was placed in a quartz tube furnace and then heated at 650 °C for 8 h under the flow of H 2 /Ar (5 vol % H 2 ). After the reductive heating with Mg metal, the heated sample was stirred with 2.0 M HCl solution for 4 h to selectively etch out the MgO phase in order to obtain MgO-free reduced TiO (named T1) with high porosity. …”
Section: Experimental Methodsmentioning
confidence: 99%
“…Kim et al reported a Pt/reduced TiO 2− x -loaded filter paper carbon (FPC) to degrade gas-phase acetaldehyde (CH 3 CHO). 189 First, FPC was prepared by the carbonization of a filter paper at 400–1000 °C under Ar gas flow (FPC- y , where y is the carbonization temperature). Next, reduced TiO 2− x (rT- z , where z is the molar amount of Mg) was synthesized through a magnesiothermic reduction of commercial anatase TiO 2 (CT) at 500 °C for 8 h under 5% H 2 /Ar gas flow.…”
Section: Energy Conversionmentioning
confidence: 99%
“…49 Compared to TiO 2 nanoparticles calcined at high temperature, the yellow TiO 2 had abundant oxygen vacancies and Ti 3+ , which led to better electron transfer conductivity, increased visible light absorption and higher conduction band potential. 50 Xi et al 51 synthesized defective TiO 2 nanocrystals via a simple, mild and green sol–gel hydrothermal method. The prepared samples had a high specific surface area of 173.6 m 2 g −1 and perfect crystallinity of anatase phase without any calcination treatment.…”
Section: Preparation Of Tio2−xmentioning
confidence: 99%